RESEARCH ON SAFETY ASSESSMENT METHOD FOR BOX GIRDER OF BRIDGE AND GANTRY CRANE - XIONG Gang; WU Xiao; LUO Tao; LUO YouHong (Jixie qiangdu)
Taking box girder structure of 36 t container gantry crane as research object,and combining with the finite element analysis results of crane structure,it carried out a safety assessment for the cracks on box girder structure using level 2fracture assessment method. Evaluation results showed that the six surface cracks were all in the safe range. It established the model of crack,determined evaluation parameters,made evaluation calculation,and drew FAD figure,which explored a set of safety assessment processes and methods suitable for the steel structure of crane. It has realistic meaning to guide crane structure safety assessment and eventually to form a unified standard.